The role of leadership in transitional states : the cases of Lebanon, Israel-Palestine / Anastasia Filippidou, editor. - Filippidou, Anastasia (Strategic Studies Institute and U.S. Army War College Press, 2014)
"Leadership is dynamic; it is a continuous process and ever-changing relationship between numerous different factors. The research focuses on political leadership in transitional situations and the efforts of leadership in the transformation process from weak and fragmented states or communities to peaceful and viable states. These concepts are tested vis-à-vis U.S. foreign policy toward the Middle East, which will have to be adaptive and flexible on the one hand in order to show ability and will; but will also have to be consistent on the other, so that it can show commitment and impartiality"--Publisher's web site.